2021
DOI: 10.26740/paramasastra.v8n1.p1-19
|View full text |Cite
|
Sign up to set email alerts
|

Efl Students Metacognitive Strategies in Online-Based Learning: In Relation to Their Writing Quality

Abstract: This study aimed to investigate the correlation between students metacognitive strategies and their writing quality in an online learning context. It involved 35 English-major students at one of the state universities in East Java, Indonesia. A metacognitive strategies questionnaire and a writing rubric were used as the instruments of this study. Then, the data obtained were analyzed by using a descriptive statistic and a Spearman rho correlation analysis with SPSS 21 program. The results reported that the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Table 7 indicates the frequency of monitoring strategies in TRMI and IMP groups. The IMP group was more involved in reflection than TRMI, as shown in the frequency of the items that required thinking (items 11,14,18,19). It can be assumed that reflection can be cultivated among learners and can lead to using metacognitive strategies associated with the monitoring dimension in online writing classes.…”
Section: Frequency Of Metacognitive Strategies In Online Writing Coursementioning
confidence: 99%
“…Table 7 indicates the frequency of monitoring strategies in TRMI and IMP groups. The IMP group was more involved in reflection than TRMI, as shown in the frequency of the items that required thinking (items 11,14,18,19). It can be assumed that reflection can be cultivated among learners and can lead to using metacognitive strategies associated with the monitoring dimension in online writing classes.…”
Section: Frequency Of Metacognitive Strategies In Online Writing Coursementioning
confidence: 99%
“…In Indonesian context, while many studies have examined how EFL students use metacognitive reading strategies (Indriyani & Pertiwi, 2021;Fitrianti & Susanti, 2021), there is currently a dearth of research focused on EFL teachers, particularly pre-service teachers. Existing studies involving EFL teachers in the use of these reading strategies revealed mixed findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, there has been very limited research on the role of EFL teachers in using these online strategies. Moreover, research that focuses on pre-service EFL teachers is still very rare, especially in Indonesian context (Indriyani & Pertiwi, 2021;Fitrianti & Susanti, 2021). Research in this area is very important to do because in addition to further support the body of knowledge in online reading, the findings of the research can be used as a reference in improving quality of English learning processes through application of appropriate online reading strategies.…”
Section: Introductionmentioning
confidence: 99%